Optimization of Formula and In Vitro Activity Testing of O/W Lotion Cosmetic Formulations Containing Ethanol Extract of Cat's Whiskers Leaves (Orthosiphon aristatus) as Sunscreen - Yasir, Angga Saputra; Suryaneta, Suryaneta; Putri, Tikarahayu; Saputra, Iwan; Handayani, Kiki; Zulaicha, Annisaa; Sari, Indah Puspita; Nurhayati, Veni; Sholeha, Aida (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Exposure to ultraviolet (UV) radiation from sunlight can induce erythema, sunburn, and skin sensitivity, culminating in dermal damage. The application of sunscreen mitigates potential skin harm resulting from solar radiation. This investigation aims to ascertain the optimal formulation for lotion preparations incorporating Orthosiphon aristatus leaf extract and evaluate the sunscreen efficacy of said formulations through in vitro testing. Extraction procedures involved ethanol maceration, followed by phytochemical characterization of the resultant extract. Formulation of the extract into oil-in-water (O/W) lotion preparations was executed, with optimization conducted utilizing the Simplex Lattice Design (SLD) method, incorporating varied concentrations of stearic acid, cetyl alcohol, and olive oil to assess their impact on lotion viscosity, spreadability, and adhesion. Subsequent evaluation encompassed in vitro assessment of sunscreen activity for both the lotion and extract. Findings revealed the presence of flavonoids, saponins, and tannins in the extract. Optimal lotion formulation, determined via the SLD method, yielded concentrations of 2.00, 4.22, and 8.78 for stearic acid, cetyl alcohol, and olive oil, respectively. Formulation optimization was guided by minimizing viscosity while maximizing spreadability and adhesion. Confirmation studies underscored the predictive capacity of the SLD method in determining viscosity, spreadability, and adhesion of the cat's whiskers leaf extract lotion. SPF values for the extract and lotion were recorded as 33.63 ± 0.963 and 2.54 ± 0.001, respectively, at a concentration of 30,000 ppm.